Relación entre inteligencia lingüística y comprensión de textos en inglés en estudiantes de la I.E. Manuel de Piérola Castro, Celendín-2021 - Díaz Rodríguez, Mercedes Helen (2022)
The purpose of the present investigation was to determine the relationship between linguistic intelligence and English text comprehension in students of the I.E Manuel de Piérola Castro -2021. The research was a quantitative approach, non-experimental research, with a descriptive correlational design. The sample was of a census type and consisted of 42 students in the fifth year of secondary school. Two instruments were used to collect the information: a questionnaire with 20 items to measure linguistic intelligence and a test with 30 items to measure literal, inferential and critical text comprehension in English. The validation of the instruments was determined through Cronbach's Alpha statistical analysis, which demonstrated the reliability of the instruments developed. By tabulating the data, it was possible to contrast that the working hypothesis is fulfilled, that is, that linguistic intelligence shows a significant correlation between the variables studied, linguistic intelligence and comprehension of texts in English in the students belonging to this educational institution.